Nitrogen utilization by corn as affected by green manures and nitrogen and phosphorus fertilizers - Silva, Edson Cabral da; Muraoka, Takashi; Villanueva, Felipe Carlos Alvarez; Espinal, Freddy Sinencio Contreras (Pesquisa Agropecuaria Brasileira, 2010)
The objectives of this work were to evaluate corn (Zea mays) nitrogen (N) utilization from the green manure crops sunnhemp (Crotalaria juncea) and millet (Pennisetum glaucum L.) and from urea, and to calculate the contribution of soil N to the mineral nutrition of corn, as affected by nitrogen and phosphorus mineral fertilizers. The experiment was conducted in a greenhouse, in pots with 5 kg of soil (Rhodic Hapludox). The experimental design was completely randomized, with 32 treatments and four replicates, in a 4x4x2 factorial array. The treatments were combinations of four N rates as urea: 0, 0.75, 1.50 and 2.25 g N per pot (labeled or not with 15N); four P rates as triple superphosphate: 0, 0.175, 0.350 and 0.700 g P per pot; and sunnhemp and millet labeled or not with 15N. Green manure dry matter provided 1 g N per pot. Corn plants were evaluated for dry mass yield, accumulated N, and N utilization from green manures, urea, and the soil. The mineral fertilizer supplied the largest amount of N to the corn plants, followed by N from soil and from green manures. The N utilization from sunnhemp by corn plants was greater than the N utilization from millet. The phosphorus application increased the assimilation of N from urea and from green manures.